2021
DOI: 10.1111/jocn.15829
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric home confinement due to COVID‐19: Somatic and anxiety spectrum consequences

Abstract: Aims and Objectives We aimed to determine the impact of COVID‐19 related home confinement on the paediatric population by focusing on anxiety, behavioural disturbances and somatic symptoms. Background To limit the spread of the COVID‐19 outbreak, governments have imposed nationwide lockdowns to prevent direct contact; this has affected everyday lives and activities such as attending school classes. Such isolation may have impacted children’s anxiety levels. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 51 publications
0
20
0
1
Order By: Relevance
“…Another study found that adolescent girls had higher levels of depression, anxiety, and stress (Tamarit et al, 2020). However, in contrast to this information, two studies concluded that boys had higher anxiety scores (Francisco et al, 2020;García-Adasme et al, 2021).…”
Section: Gender Differencesmentioning
confidence: 89%
See 2 more Smart Citations
“…Another study found that adolescent girls had higher levels of depression, anxiety, and stress (Tamarit et al, 2020). However, in contrast to this information, two studies concluded that boys had higher anxiety scores (Francisco et al, 2020;García-Adasme et al, 2021).…”
Section: Gender Differencesmentioning
confidence: 89%
“…Of the 27 studies that make up this review, seven concluded that age could be considered a risk factor for different emotional problems. Of these seven studies, three found that children over the age of 7, pre-adolescents, and adolescents scored higher in anxiety (Castillo-Martínez et al, 2020;García-Adasme et al, 2021;Lavigne-Cerván et al, 2021). Thus, Pizarro-Ruiz and Ordóñez-Camblor (2021) concluded that adolescents had higher rates of anxiety, depression, and emotion-regulation problems.…”
Section: Age Differencesmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, knowing someone who died from COVID-19 was associated with sleeping disturbances, as well as the statement “being afraid or anxious about going outside.” Accordingly, it has been shown that children who knew someone who had suffered from COVID-19 at home or whose parent was directly involved in the pandemic, presented higher anxiety scores ( 18 ). Of note, anxiety and irritability were reported for the majority of children and adolescents, being the youngest the most affected.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been recently described ( 14 , 17 , 19 , 20 ) and underline the need to consider how we communicate information to children and help them manage this information. Furthermore, it has been shown that anxiety and depressive symptoms and other negative outcomes were more likely in children whose parents reported higher levels of stress, depression or were unemployed ( 18 , 20 23 ), and that those were often more important among the youngest ones ( 20 ). Thus, supporting parents' mental health and providing them with accurate information, strategies and support to cope with lockdown is essential to protect their children's mental health ( 24 , 25 ).…”
Section: Discussionmentioning
confidence: 99%